Differentiation, Promotion, and Interest in Building Spiritual Capital Muzzaki - Hartono, Setyo Budi (Jurnal Iqtisaduna, 2018)
The purpose of this study is to determine the formulation of variables that influence between differentiation, promotion, and zakat interest in forming spiritual capital in muzakki. Differentiation, promotion, and interest in this study use a religious approach in developing indicators that are used to explain the spiritual capital in muzakki. Purposive sampling is a technique used in this study, namely as many as 100 muzakki people who channel zakat through the National Zakat Amil Agency (BAZNAS) in Indonesia. Testing of research data using Partial Least Square (PLS). The results of this study indicate that differentiation and promotion leads to increased zakat interest, but differentiation and promotion does not lead to an increase in spiritual capital in muzaaki. The formation of spiritual capital in muzakki is explained through interest formed from the differentiation and promotion that has been carried out by the Amil Zakat Agency in Indonesia (BAZNAS). From the results of PLS testing shows that the influence of differentiation mediated by promotion has a greater influence on the interest of muzakki to tithe. Promotion plays a role as a link between differentiation and the formation of zakat interests to become a spiritual capital in muzakki.